Effective management strategies for patients with marginal zone lymphoma. (May 2018) - Rosand, Cecilia B; Valla, Kelly; Flowers, Christopher R; Koff, Jean L
Marginal zone lymphoma (MZL) is an uncommon indolent lymphoma classified into subtypes based on primary site of involvement: splenic, nodal and extranodal. MZLs' relative rarity has largely precluded adoption of a standard management strategy. Here, we provide an overview of the epidemiology, clinical behavior and therapeutic approaches for each subtype. Biologic insights into lymphomagenesis have identified B-cell receptor signaling as a rational therapeutic target. Recent clinical data suggest that novel agents targeting this pathway, including the Bruton's tyrosine kinase inhibitor, ibrutinib, show significant promise in treatment of relapsed MZL. More work is needed to evaluate these agents' activity in the front-line setting, possible combination regimens and the impact of resistance to B-cell receptor-targeted agents in order to optimize therapy in MZL.